Influence of Physical Activity Interventions on Body Representation: A Systematic Review - Srismith, Duangkamol; Wider, Leona-Magdelena; Wong, Hong Yu; Zipfel, Stephan; Thiel, Ansgar; Giel, Katrin Elisabeth; Behrens, Simone Claire (Frontiers in Psychiatry, 2020)
Distorted representation of one's own body is a diagnostic criterion and core psychopathology of disorders such as anorexia nervosa and body dysmorphic disorder. Previous literature has raised the possibility of utilising physical activity intervention (PI) as a treatment option for individuals suffering from poor body satisfaction, which is traditionally regarded as a systematic distortion in ‘body image’. In this systematic review, conducted according to the PRISMA statement, the evidence on effectiveness of PI on body representation outcomes is synthesised. We provide an update of 34 longitudinal studies evaluating the effectiveness of different types of PIs on body representation. No systematic risk of bias within or across studies were identified. The reviewed studies show that the implementation of structured PIs may be efficacious in increasing individuals’ satisfaction of their own body, and thus improving their subjective body image related assessments. However, there is no clear evidence regarding an additional or interactive effect of PI when implemented in conjunction with established treatments for clinical populations. We argue for theoretically sound, mechanism-oriented, multimethod approaches to future investigations on body image disturbance. Specifically, we highlight the need to consider expanding the theoretical framework for the investigation of body representation disturbances to include further body representations besides body image.